The Role of Preschool Teachers in Enhancing Imaginative Free-Play Activities in Preschool - Viswanathan, Thivasenikumari; Rahman, Mohd Nazri Abdul (UPI Kampus Cibiru, 2024)
The goal of this study is to investigate preschool teachers' roles in contributing towards the Imaginative Free-Play activities in the preschool curriculum learning activities, to explore and comprehend preschool teachers' roles in the concept of creative teaching, and to comprehend preschool teachers' roles in Imaginative Free-Play activities in order to improve preschool children's learning and development processes. This exploratory study adopted a qualitative method of inquiry to provide an in-depth understanding of the area being investigated. Interviews and observations of four preschool teachers, who were purposefully selected from a private preschool, were used to collect data. Findings revealed that all the preschool teachers in this study expressed their views that preschool teachers played multi-character roles in conducting Imaginative Free-Play activities, and it is regarded as fundamental to the child's learning and development to be creative. All the teachers also foster creative ideas to stimulate children’s ideas during the teaching and learning process. Therefore, preschool teachers play a few important roles in order for children to think and act creatively while also being problem solvers.